First report of Melampsora epitea causing stem cankers on Salix pentandra in Alberta, Canada - Ramsfield, Tod D.; Feau, Nicolas; Tanguay, Philippe; Hamelin, Richard C.; Herath, Padmini; Bozic, Toso (Frontiers in Forests and Global Change, 2023)
In June, 2021, a rust disease causing cankers was discovered on laurel leaf willow (Salix pentandra) near Slave Lake, Alberta. Bright yellow urediniospores were observed on uredia that were present on catkins, leaves and stems. All Melampsora spp. previously reported in Canada are recorded as infecting leaves; therefore, further investigation using DNA sequence data from the internal transcribed spacer (ITS) ribosomal RNA region was conducted. Sequencing and BLAST analysis of the material from the sample resulted in a 99.3% sequence identity match to Melampsora epitea “Mel J” collected from Larix laricina in New York State. To further assess the relationship between this specimen and other Melampsora spp. collected from Canada, samples from herbarium specimens of willow leaves infected by Melampsora spp. were retrieved from the mycological herbariums located at the Laurentian Forestry Centre (QFB) and the Northern Forestry Centre (CFB, WINF(M)). DNA extracted from these herbarium specimens was used to conduct a phylogenetic analysis. The ITS sequence from the herbarium sample WINF(M)7356 (described as M. abieti-capraearum from Manitoba) had 100.0% identity with the Alberta sample. Additionally, specimens WINF(M)11892 (Melampsora sp. from Manitoba) and CFB8931 (Melampsora sp. from the Yukon) had 99.0% sequence identity with the Alberta sample. From these results we applied the identity of M. epitea to the rust discovered in Slave Lake, AB. With the current emphasis on willows for bioenergy production in Canada, growers must remain vigilant for this pathogen and the damages it could cause to willow plantations.